Synthesis of novel pyrazolo[3,4-b]quinoline-bisphosphonic acids and an unexpected intramolecular cyclization and phosphonylation reaction - Teixeira, Fatima (2021)
ABSTRACT: Novel pyrazolo[3,4-b]quinoline alpha-ketophosphonic and hydroxymethylenebisphosphonic acid compounds were synthesized using different methodologies, starting from 2-chloro-3-formylquinoline 1. New phosphonic acid compounds were obtained as N-1 derivatives with a side chain with 1 or 3 (n = 1 or 3) methylene groups. All phosphonic acid compounds and their corresponding ester and carboxylic acid precursors were fully characterized, and their structures elucidated by spectroscopic data, using NMR techniques and infrared and high-resolution mass spectroscopy. During the process to obtain the N-1 substituted derivative with two methylene groups (n = 2) in the side chain, an unexpected addition-cyclization cascade reaction was observed, involving the phosphonylation of an aromatic ring and the formation of a new six-member lactam ring to afford a tetracyclic ring system. This was an unexpected result since other pyrazolo[3,4-b]quinoline derivatives and all corresponding pyrazolo[3,4-b]pyridine derivatives already prepared, under similar experimental conditions, did not undergo this reaction. This domino reaction occurs with different phosphite reagents but only affords the six-member ring. The spectroscopic data allowed the identification of the new synthesized tetracyclic compounds and the X-ray diffraction data of compound 11 enabled the confirmation of the proposed structures.